An Ayurvedic Approach to The Management of Chronic Kidney Disease Secondary to Genito Urinary Tuberculosis – A Single Case Study - Krishna P, Anu; Sasanoor, Mahantagouda Shivanna; G M, Maithri; M.D, Beena; V. Binorkar, Sandeep; J, Divya; Chandra S, Jagadeep; Kumar B G, Chethan; K T, Vadiraj; K. M, Anil Kumar (Journal of Neonatal Surgery, 2025)
Introduction: Chronic Kidney Disease (CKD) presents a major global health burden, with increasing incidence and limited therapeutic options in conventional medicine. ayurveda, the ancient Indian system of medicine, offers holistic and individualized approaches that may provide supportive and potentially restorative outcomes in CKD management. this case study aims to explore the clinical efficacy of ayurvedic interventions in the management of a patient diagnosed with ckd secondary to genito urinary tuberculosis, highlighting symptomatic relief, improvement in biochemical parameters, and overall quality of life. Methodology: a 35-year-old male patient diagnosed with stage 3 ckd associated with bladder neck dysfunction with history of genito urinary tb, presented with symptoms dribbling of urine, increased frequency of micturition,pain and burning sensation during micturition, and elevated serum creatinine, urea. a comprehensive treatment protocol was administered, comprising Yogabasthi, Avagaha Sweda, Adhonabhi Pichu alongside dietary and lifestyle modifications aligned with Pathya-apathya. Result: over a treatment span of 3 months the patient exhibited notable improvements in renal biochemical parameters and subjective symptoms. no adverse events were observed during or post-treatment. Discussion: this single case study underscores the potential of ayurvedic interventions in improving clinical outcomes in ckd and calls for further clinical research through well-designed, large-scale studies to validate efficacy, safety, and long-term outcomes.